Scale and corrosion inhibitor for water and preparation method thereof
By using a water scale corrosion inhibitor containing modified oxidized starch, polyepoxysuccinic acid and water-soluble zinc salt in the circulating water system, the scale and corrosion problems of circulating water under high hardness and alkalinity conditions are solved, and a phosphorus-free environmental protection and high-efficiency scale corrosion inhibition effect is achieved.
Patent Information
- Application Number
- CN202510285183.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-11
AI Technical Summary
circulating water is prone to scaling and corrosion problems under conditions of high hardness and alkalinity, and the existing phosphorus-free scale-retardant corrosion inhibitors still have room for improvement in environmental protection and application.
A water-based scale corrosion inhibitor is used, and the composition includes 10-30% scale inhibitor, 35-40% hydrolyzed polymaleic anhydride, 12-20% acrylic-2-acrylamide-2-methylpropanesulfonic acid copolymer, 4-7.5% water-soluble zinc salt and residual water. Among them, the scale inhibitor is polyepoxysuccinic acid, polyaspartic acid or modified oxidized starch, and the water-soluble zinc salt is zinc sulfate, zinc nitrate or zinc chloride. The modified oxidized starch is oxidized by overlapping potassium permanganate and hydrogen peroxide, graft aspartic acid and lysine, coupled with β-cyclodextrin, and finally modified by sonication.
This scale-resistance corrosion inhibitor effectively prevents scale and corrosion under high hardness and alkalinity conditions, ensures the safe operation of the circulating water system, and solves the problem of phosphorus-free environmental protection, and has broad application prospects.
Smart Images

Figure BDA0005306902760000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scale and corrosion inhibitors, and in particular to a scale and corrosion inhibitor for water and a preparation method thereof. Background Art
[0002] The circulating water system self-drainage is de-hardened and desalted and reused in the circulating water system. The main components of the common scale inhibitors and corrosion inhibitors used include scale inhibitors, dispersants, corrosion inhibitors, etc. This common scale inhibitor and corrosion inhibitor has a good effect on the scale and corrosion inhibition treatment of circulating water systems in alkaline environments. At present, phosphorus-containing agents occupy the main market in the field of industrial circulating water treatment agents. After decades of development, phosphorus-containing agents have become quite mature, low-cost, and the treatment effect fully meets the standards of relevant industries. However, with the discharge of phosphorus-containing circulating water, on the one hand, it causes eutrophication of water bodies and destroys the water quality ecology, and on the other hand, it also increases the management and reuse of circulating water discharge. In recent years, with the improvement and strengthening of people's and society's environmental awareness, the use of phosphorus-containing agents has been restricted by various manufacturers. The research and development and production of phosphorus-free scale inhibitors and corrosion inhibitors have broad application value for the water treatment industry.
[0003] The use of oxidized starch in water treatment scale inhibitors has been reported, but it appears in the form of a uniform composition, mixed with other ingredients for water treatment. For example, Chinese invention patent CN102452723B discloses a phosphorus-free composite scale inhibitor, which is made by mixing 10%-13% polyaspartic acid, 25%-28% sodium lignin sulfate, 10%-13% oxidized starch, and 50%-55% deionized water. Chinese invention patent CN110342654B discloses a new type of phosphorus-free corrosion inhibitor, which is made of the following raw materials in mass percentage: 30-80% modified chitosan quaternary ammonium salt mixture, 10-50% oxidized starch mixture, and 10-25% alkylamine emulsion. At present, there is no report on the scale and corrosion inhibition performance of oxidized starch after modification. Summary of the invention
[0004] The purpose of the present invention is to provide a water-based scale and corrosion inhibitor and a preparation method thereof, which can solve the scaling and corrosion problems generated when circulating water is running under conditions of high hardness and alkalinity, ensure the safe operation of the circulating water system under the condition of small amount of sewage discharge, solve the problem of phosphorus-free environmental protection, and have broad application prospects.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The present invention provides a water scale and corrosion inhibitor, comprising the following components in percentage by mass:
[0007] 10-30% antiscalant;
[0008] 35-40% hydrolyzed polymaleic anhydride;
[0009] 12-20% acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer;
[0010] 4-7.5% water-soluble zinc salt;
[0011] and the balance of water.
[0012] As a further improvement of the present invention, the scale inhibitor is at least one of polyepoxysuccinic acid, polyaspartic acid, and modified oxidized starch.
[0013] As a further improvement of the present invention, the water-soluble zinc salt is at least one of zinc sulfate, zinc nitrate, zinc chloride and zinc acetate.
[0014] As a further improvement of the present invention, the preparation method of the modified oxidized starch is as follows:
[0015] S1. Preparation of composite oxidized starch: corn starch, potassium permanganate and sulfuric acid were added to water, heated and stirred to react, the pH value of the solution was adjusted to, hydrogen peroxide was continued to be added dropwise, a catalyst was added, microwave treatment was performed, the reaction was continued at a temperature of 100 °C, the pH value of the solution was adjusted to 100 °C, filtration was performed, washing was performed, and drying was performed to obtain composite oxidized starch;
[0016] S2. Grafting aspartic acid and lysine: adding composite oxidized starch to water, adding NHS and EDC, stirring to activate, adding aspartic acid and lysine, stirring to react, dialyzing, freeze-drying, and obtaining grafted composite oxidized starch;
[0017] S3. Chlorination: adding the grafted composite oxidized starch to the ionic liquid, adding thionyl chloride, stirring the reaction, adding ethanol to precipitate, filtering, washing the solid, and drying to obtain a modified grafted composite oxidized starch;
[0018] S4. Reaction with cyclodextrin: dissolving β-cyclodextrin in water, adding modified grafted composite oxidized starch and triethylamine, heating and stirring the reaction, centrifuging, washing, and drying to obtain cyclodextrin-modified grafted composite oxidized starch;
[0019] S5. Ultrasonic treatment: adding the prepared cyclodextrin-modified grafted composite oxidized starch into water, ultrasonically treating it, and drying it to obtain modified oxidized starch.
[0020] As a further improvement of the present invention, the mass ratio of corn starch, potassium permanganate, sulfuric acid, hydrogen peroxide and catalyst in step S1 is 20-30:4-7:3-5:10-12:0.5-1, the catalyst is cupric chloride or copper sulfate, the temperature of the heating and stirring reaction is 50-60°C, the time is 2-4h, and the power of the microwave treatment is 1000-1500W, and the time is 1-3h.
[0021] As a further improvement of the present invention, the mass ratio of the composite oxidized starch, NHS, EDC, aspartic acid and lysine in step S2 is 12-15:3-4:3-4:5-7:2-4, the dialysis bag pore size used in the dialysis is 8-12KDa, and the dialysis time is 10-12h.
[0022] As a further improvement of the present invention, the mass ratio of the grafted composite oxidized starch, dithionyl chloride, and ionic liquid in step S3 is 10:3-5:30-40, the stirring reaction time is 2-4 hours, and the ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium dihydrogen phosphate, and 1-butyl-3-methylimidazolium hydrogen sulfate.
[0023] As a further improvement of the present invention, in step S4, the mass ratio of β-cyclodextrin, modified grafted composite oxidized starch and triethylamine is 3-5:12-15:2-4, and the temperature of the heating and stirring reaction is 50-60° C. and the time is 3-5 h.
[0024] As a further improvement of the present invention, the power of the ultrasonic treatment in step S5 is 1500-2500 W, and the time is 20-30 min.
[0025] The present invention further protects a method for preparing the above-mentioned water scale and corrosion inhibitor, comprising the following steps:
[0026] (1) adding hydrolyzed polymaleic anhydride to water, then adding a water-soluble zinc salt and stirring, mixing evenly to obtain a solution;
[0027] (2) At room temperature, acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer and scale inhibitor are added to the solution and stirred evenly to prepare a scale inhibitor and corrosion inhibitor for water.
[0028] The present invention has the following beneficial effects:
[0029] Polyaspartic acid is a water-soluble polymer substance synthesized by artificial biomimetic synthesis. It is phosphorus-free, non-toxic, pollution-free and completely biodegradable. It is a green chemical. It has extremely strong chelating, dispersing and adsorption effects and excellent compatibility.
[0030] Polyepoxysuccinic acid is a phosphorus-free, non-nitrogen, "green" environmentally friendly multi-scale inhibitor and corrosion inhibitor. Polyepoxysuccinic acid has good scale inhibition and dispersion properties for calcium carbonate, calcium sulfate, barium sulfate, calcium fluoride and silica scale in water, and its scale inhibition effect is better than that of commonly used organic phosphine scale inhibitors. The combination of polyepoxysuccinic acid and phosphonates has a good synergistic effect. At the same time, polyepoxysuccinic acid has a certain corrosion inhibition effect and is a multi-scale inhibitor; polyepoxysuccinic acid (PESA) is a nitrogen-free, non-phosphorus organic compound with dual effects of scale inhibition and corrosion inhibition, good biodegradability and suitable for high-alkali, high-metal content water systems. It is a green water treatment chemical.
[0031] Starch is a natural high molecular weight cyclic polymer with the characteristics of "hydrophilic outer cavity and hydrophobic inner cavity". The large number of hydroxyl groups on its outer side have a chelating effect on high-valent metal ions and have certain corrosion and scale inhibition properties. However, its performance needs to be further improved, and its poor water solubility limits its wide application.
[0032] The present invention prepares a modified oxidized starch. By overlapping the oxidation of starch with potassium permanganate and hydrogen peroxide, potassium permanganate is used as an oxidant to oxidize the starch, so that oxidized starch with high carboxyl content and low depolymerization degree can be prepared. Hydrogen peroxide can easily penetrate deep into starch particles and cause oxidation, so that starch molecules are broken at C2 and C3 to depolymerize the starch. Generally, the oxidation degree is low and the depolymerization degree is high. By using the two to overlap and oxidize alternately, the purpose of increasing the carboxyl content and appropriately reducing the molecular weight of starch can be achieved, thereby improving the solubility of starch on the one hand, and also improving the scale and corrosion inhibition performance of the obtained product. Excessive hydrogen peroxide is eventually decomposed into water, which will not affect the purity of the product and the environment, and is an ideal green process.
[0033] Furthermore, the present invention adopts aspartic acid and lysine grafted composite oxidized starch, which significantly improves the scale inhibition and corrosion inhibition effect. The dicarboxyl structure of aspartic acid and the diamino structure of lysine provide abundant chelating sites for complexing metal ions, greatly improving the chelating efficiency of metal ions, and is safer and more environmentally friendly, avoiding eutrophication of water bodies and secondary pollution of emissions. It has a strong chelating ability for metal ions and has the dual effects of corrosion inhibition and scale inhibition. Therefore, it has a good scale inhibition effect on scale-forming salts such as calcium carbonate, calcium sulfate, barium sulfate, and calcium phosphate, and the scale inhibition rate for calcium carbonate can reach 100%.
[0034] The hydroxyl groups on the grafted composite oxidized starch are chlorinated and coupled with β-cyclodextrin. β-cyclodextrin has a hydrophilic exterior and a hydrophobic interior cavity, which can encapsulate scale-forming ions (such as Ca 2+ Mg 2+) or scale precursor molecules are enclosed in its cavity, thereby preventing these ions from combining with anions such as carbonate to form scale. In addition, the functional groups in its polymer structure (such as hydroxyl, carboxyl, etc.) can interact with the ions on the surface of the scale crystal, interfering with the normal growth of the scale crystal, causing lattice distortion and reducing the adhesion of the scale layer.
[0035] The cyclodextrin-modified grafted composite oxidized starch is subjected to ultrasonic treatment, and the surface of the starch particles is deformed to form holes and grooves that improve water permeability. The enhanced permeability promotes the expansion and size increase of the starch particles, so that the prepared modified oxidized starch can form a protective film on the metal surface through physical adsorption or chemical adsorption, preventing the corrosive medium from contacting the metal. It has strong steric hindrance, can isolate and resist the attack of corrosive ions, and has good alkali resistance, thereby achieving corrosion inhibition.
[0036] The water scale and corrosion inhibitor of the present invention can solve the scaling and corrosion problems generated when circulating water is running under conditions of high hardness and alkalinity, ensure the safe operation of the circulating water system under the condition of small amount of sewage discharge, solve the problem of phosphorus-free environmental protection, and has broad application prospects. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] NHS, N-hydroxysuccinimide; EDC, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride.
[0039] Preparation Example 1 Preparation of modified oxidized starch
[0040] The following steps are involved:
[0041] S1. Preparation of composite oxidized starch: 20 g corn starch, 4 g potassium permanganate, and 3 g sulfuric acid were added to 500 mL water, heated to 50 ° C, stirred for reaction for 2 h, the pH value of the solution was adjusted to 3, 10 g hydrogen peroxide was added dropwise, 0.5 g copper chloride was added, and the power was 1000 W microwave treatment for 1 h, and the reaction was continued for 2 h at a temperature of 1 g sodium bisulfite was added to terminate the reaction, and the pH value of the solution was adjusted to 5.5, filtered, washed, and dried to obtain composite oxidized starch;
[0042] S2. Grafting aspartic acid and lysine: 12 g of composite oxidized starch was added to 200 mL of water, 3 g of NHS and 3 g of EDC were added, and the mixture was stirred for activation for 30 min, 5 g of aspartic acid and 2 g of lysine were added, and the reaction was stirred for 10 h, and the mixture was dialyzed for 10 h using a dialysis bag with a pore size of 8 KDa, and freeze-dried to obtain a grafted composite oxidized starch;
[0043] S3. Chlorination: 10 g of grafted composite oxidized starch was added to 30 g of 1-butyl-3-methylimidazole dihydrogen phosphate ionic liquid, 3 g of thionyl chloride was added, the reaction was stirred for 2 h, ethanol was added to the ethanol content of the system was 80 wt %, precipitated for 1 h, filtered, the solid was washed and dried to obtain a modified grafted composite oxidized starch;
[0044] S4. Reaction with cyclodextrin: 3 g of β-cyclodextrin was dissolved in 150 mL of water, 12 g of modified grafted composite oxidized starch and 2 g of triethylamine were added, heated to 50 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain cyclodextrin-modified grafted composite oxidized starch;
[0045] S5. Ultrasonic treatment: add 1 g of cyclodextrin-modified grafted composite oxidized starch into 50 mL of water, perform ultrasonic treatment at 1500 W for 20 min, and dry to obtain modified oxidized starch.
[0046] Preparation Example 2 Preparation of modified oxidized starch
[0047] The following steps are involved:
[0048] S1. Preparation of composite oxidized starch: 30 g corn starch, 7 g potassium permanganate, and 5 g sulfuric acid were added to 500 mL water, heated to 60 ° C, stirred for 4 h, the pH value of the solution was adjusted to 4, 12 g hydrogen peroxide was added dropwise, 1 g copper sulfate was added, and the power was 1500 W microwave treatment for 3 h, and the reaction was continued for 4 h at a temperature of 1 g. 1 g sodium bisulfite was added to terminate the reaction, the pH value of the solution was adjusted to 6, filtered, washed, and dried to obtain composite oxidized starch;
[0049] S2. Grafting aspartic acid and lysine: 15 g of composite oxidized starch was added to 200 mL of water, 4 g of NHS and 4 g of EDC were added, and the mixture was stirred for activation for 30 min, 7 g of aspartic acid and 4 g of lysine were added, and the reaction was stirred for 12 h, and the mixture was dialyzed for 12 h using a dialysis bag with a pore size of 12 KDa, and freeze-dried to obtain a grafted composite oxidized starch;
[0050] S3. Chlorination: 10 g of grafted composite oxidized starch was added to 40 g of 1-butyl-3-methylimidazolium bromide ionic liquid, 5 g of thionyl chloride was added, the reaction was stirred for 4 h, ethanol was added to the ethanol content of the system was 80 wt %, precipitated for 1 h, filtered, the solid was washed and dried to obtain a modified grafted composite oxidized starch;
[0051] S4. Reaction with cyclodextrin: 5 g of β-cyclodextrin was dissolved in 150 mL of water, 15 g of modified grafted composite oxidized starch and 4 g of triethylamine were added, heated to 60 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain cyclodextrin-modified grafted composite oxidized starch;
[0052] S5. Ultrasonic treatment: add 1 g of cyclodextrin-modified grafted composite oxidized starch into 50 mL of water, perform ultrasonic treatment at 2500 W for 30 min, and dry to obtain modified oxidized starch.
[0053] Preparation Example 3 Preparation of modified oxidized starch
[0054] The following steps are involved:
[0055] S1. Preparation of composite oxidized starch: 25 g corn starch, 5.5 g potassium permanganate, and 4 g sulfuric acid were added to 500 mL water, heated to 55 ° C, stirred for 3 h, the pH value of the solution was adjusted to 3.5, 11 g hydrogen peroxide was added dropwise, 0.7 g copper sulfate was added, the power was 1200 W microwave treatment for 2 h, the heat was kept for 3 h, 1 g sodium bisulfite was added to terminate the reaction, the pH value of the solution was adjusted to 5.7, filtered, washed, and dried to obtain composite oxidized starch;
[0056] S2. Grafting aspartic acid and lysine: 13 g of composite oxidized starch was added to 200 mL of water, 3.5 g of NHS and 3.5 g of EDC were added, and the mixture was stirred for activation for 30 min, 6 g of aspartic acid and 3 g of lysine were added, and the reaction was stirred for 11 h, and the mixture was dialyzed for 11 h using a dialysis bag with a pore size of 10 KDa, and freeze-dried to obtain a grafted composite oxidized starch;
[0057] S3 chlorination: 10g of grafted composite oxidized starch was added to 35g of 1-butyl-3-methylimidazolium chloride ionic liquid, 4g of dichlorothionyl was added, the reaction was stirred for 3h, ethanol was added to the ethanol content of the system was 80wt%, precipitated for 1h, filtered, the solid was washed and dried to obtain a modified grafted composite oxidized starch;
[0058] S4. Reaction with cyclodextrin: 4 g of β-cyclodextrin was dissolved in 150 mL of water, 13 g of modified grafted composite oxidized starch and 3 g of triethylamine were added, heated to 55 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain cyclodextrin-modified grafted composite oxidized starch;
[0059] S5. Ultrasonic treatment: add 1 g of cyclodextrin-modified grafted composite oxidized starch into 50 mL of water, perform ultrasonic treatment at 2000 W for 25 min, and dry to obtain modified oxidized starch.
[0060] Comparative Preparation Example 1
[0061] Compared with Preparation Example 3, the difference is that hydrogen peroxide oxidation is not performed in step S1.
[0062] The details are as follows:
[0063] S1. Preparation of oxidized starch: Add 25 g corn starch, 5.5 g potassium permanganate and 4 g sulfuric acid into 500 mL water, heat to 55°C, stir and react for 3 h, adjust the pH value of the solution to 5.7, filter, wash and dry to obtain oxidized starch.
[0064] Comparative Preparation Example 2
[0065] Compared with Preparation Example 3, the difference is that potassium permanganate oxidation is not performed in step S1.
[0066] The details are as follows:
[0067] S1. Preparation of oxidized starch: Add 25g corn starch to 500mL water, adjust the pH value of the solution to 3.5, continue to drop 11g hydrogen peroxide, add 0.7g copper sulfate, microwave at 1200W for 2h, keep warm and continue the reaction for 3h, add 1g sodium bisulfite to terminate the reaction, adjust the pH value of the solution to 5.7, filter, wash, and dry to obtain oxidized starch.
[0068] Comparative Preparation Example 3
[0069] Compared with Preparation Example 3, the difference is that aspartic acid is not added in step S2.
[0070] The details are as follows:
[0071] S2. Grafting lysine: 13 g of composite oxidized starch was added to 200 mL of water, 3.5 g of NHS and 3.5 g of EDC were added, and the mixture was stirred for activation for 30 min. 9 g of lysine was added, and the mixture was stirred for reaction for 11 h. The mixture was dialyzed for 11 h using a dialysis bag with a pore size of 10 KDa, and freeze-dried to obtain grafted composite oxidized starch.
[0072] Comparative Preparation Example 4
[0073] Compared with Preparation Example 3, the difference is that lysine is not added in step S2.
[0074] The details are as follows:
[0075] S2. Grafting aspartic acid: Add 13 g of composite oxidized starch to 200 mL of water, add 3.5 g of NHS and 3.5 g of EDC, stir and activate for 30 min, add 9 g of aspartic acid, stir and react for 11 h, dialyze using a dialysis bag with a pore size of 10 KDa for 11 h, and freeze-dry to obtain grafted composite oxidized starch.
[0076] Comparative Preparation Example 5
[0077] Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0078] The details are as follows:
[0079] S1. Preparation of composite oxidized starch: 25 g corn starch, 5.5 g potassium permanganate, and 4 g sulfuric acid were added to 500 mL water, heated to 55 ° C, stirred for 3 h, the pH value of the solution was adjusted to 3.5, 11 g hydrogen peroxide was added dropwise, 0.7 g copper sulfate was added, the power was 1200 W microwave treatment for 2 h, the heat was kept for 3 h, 1 g sodium bisulfite was added to terminate the reaction, the pH value of the solution was adjusted to 5.7, filtered, washed, and dried to obtain composite oxidized starch;
[0080] S2. Chlorination: 10 g of composite oxidized starch was added to 35 g of 1-butyl-3-methylimidazolium chloride ionic liquid, 4 g of thionyl chloride was added, the reaction was stirred for 3 h, ethanol was added to the ethanol content of the system was 80 wt %, precipitated for 1 h, filtered, the solid was washed and dried to obtain a modified composite oxidized starch;
[0081] S3. Reaction with cyclodextrin: 4 g of β-cyclodextrin was dissolved in 150 mL of water, 13 g of modified grafted composite oxidized starch and 3 g of triethylamine were added, heated to 55 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain cyclodextrin-modified composite oxidized starch;
[0082] S4. Ultrasonic treatment: 1 g of cyclodextrin-modified composite oxidized starch was added to 50 mL of water, and ultrasonically treated at 2000 W for 25 min, and dried to obtain modified oxidized starch.
[0083] Comparative Preparation Example 6
[0084] Compared with Preparation Example 3, the difference is that steps S3 and S4 are not performed.
[0085] The details are as follows;
[0086] S1. Preparation of composite oxidized starch: 25 g corn starch, 5.5 g potassium permanganate, and 4 g sulfuric acid were added to 500 mL water, heated to 55 ° C, stirred for 3 h, the pH value of the solution was adjusted to 3.5, 11 g hydrogen peroxide was added dropwise, 0.7 g copper sulfate was added, the power was 1200 W microwave treatment for 2 h, the heat was kept for 3 h, 1 g sodium bisulfite was added to terminate the reaction, the pH value of the solution was adjusted to 5.7, filtered, washed, and dried to obtain composite oxidized starch;
[0087] S2. Grafting aspartic acid and lysine: 13 g of composite oxidized starch was added to 200 mL of water, 3.5 g of NHS and 3.5 g of EDC were added, and the mixture was stirred for activation for 30 min, 6 g of aspartic acid and 3 g of lysine were added, and the reaction was stirred for 11 h, and the mixture was dialyzed for 11 h using a dialysis bag with a pore size of 10 KDa, and freeze-dried to obtain a grafted composite oxidized starch;
[0088] S3. Ultrasonic treatment: 1 g of grafted composite oxidized starch was added into 50 mL of water, and ultrasonic treatment was performed at 2000 W for 25 min, and then dried to obtain modified oxidized starch.
[0089] Comparative Preparation Example 7
[0090] Compared with Preparation Example 3, the difference is that step S5 is not performed.
[0091] The details are as follows:
[0092] S1. Preparation of composite oxidized starch: 25 g corn starch, 5.5 g potassium permanganate, and 4 g sulfuric acid were added to 500 mL water, heated to 55 ° C, stirred for 3 h, the pH value of the solution was adjusted to 3.5, 11 g hydrogen peroxide was added dropwise, 0.7 g copper sulfate was added, the power was 1200 W microwave treatment for 2 h, the heat was kept for 3 h, 1 g sodium bisulfite was added to terminate the reaction, the pH value of the solution was adjusted to 5.7, filtered, washed, and dried to obtain composite oxidized starch;
[0093] S2. Grafting aspartic acid and lysine: 13 g of composite oxidized starch was added to 200 mL of water, 3.5 g of NHS and 3.5 g of EDC were added, and the mixture was stirred for activation for 30 min, 6 g of aspartic acid and 3 g of lysine were added, and the reaction was stirred for 11 h, and the mixture was dialyzed for 11 h using a dialysis bag with a pore size of 10 KDa, and freeze-dried to obtain a grafted composite oxidized starch;
[0094] S3 chlorination: 10g of grafted composite oxidized starch was added to 35g of 1-butyl-3-methylimidazolium chloride ionic liquid, 4g of dichlorothionyl was added, the reaction was stirred for 3h, ethanol was added to the ethanol content of the system was 80wt%, precipitated for 1h, filtered, the solid was washed and dried to obtain a modified grafted composite oxidized starch;
[0095] S4. Reaction with cyclodextrin: Dissolve 4g of β-cyclodextrin in 150mL of water, add 13g of modified grafted composite oxidized starch and 3g of triethylamine, heat to 55°C, stir and react for 4h, centrifuge, wash, and dry to obtain cyclodextrin modified grafted composite oxidized starch, that is, modified oxidized starch.
[0096] Example 1
[0097] This embodiment provides a water scale and corrosion inhibitor, comprising the following components in percentage by weight:
[0098] 15% polyepoxysuccinic acid;
[0099] 35% hydrolyzed polymaleic anhydride;
[0100] 15% acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer;
[0101] 5% zinc nitrate;
[0102] 30% water.
[0103] The preparation method comprises the following steps:
[0104] (1) adding hydrolyzed polymaleic anhydride into water, and then adding zinc nitrate and stirring for 10 minutes to obtain a solution;
[0105] (2) At room temperature, acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer and polyepoxysuccinic acid were added to the solution and stirred for 30 minutes to prepare a water scale and corrosion inhibitor.
[0106] Example 2
[0107] Compared with Example 1, the difference is that the scale inhibitor is the modified oxidized starch prepared in Preparation Example 1.
[0108] Example 3
[0109] Compared with Example 1, the difference is that the scale inhibitor is the modified oxidized starch prepared in Preparation Example 2.
[0110] Example 4
[0111] Compared with Example 1, the difference is that the scale inhibitor is the modified oxidized starch prepared in Preparation Example 3.
[0112] Comparative Example 1
[0113] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 1.
[0114] Comparative Example 2
[0115] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 2.
[0116] Comparative Example 3
[0117] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 3.
[0118] Comparative Example 4
[0119] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 4.
[0120] Comparative Example 5
[0121] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 5.
[0122] Comparative Example 6
[0123] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 6.
[0124] Comparative Example 7
[0125] Compared with Example 4, the difference is that the scale inhibitor is the modified oxidized starch prepared in Comparative Preparation Example 7.
[0126] Test Example 1 Rotating Coupon Corrosion Test
[0127] 1. Test Principle
[0128] The rotating coupon corrosion test method is a test method that uses a rotating coupon to evaluate the degree of water corrosion under given laboratory conditions. The test is conducted for a specified time by strictly controlling the specified test conditions: simulating water quality, test material, test temperature, rotation speed, etc., to select corrosion inhibitors and evaluate the corrosion inhibition effect of the formula.
[0129] 2. Test conditions
[0130] Agent: water scale and corrosion inhibitor prepared in Examples 1-4 and Comparative Examples 1-7;
[0131] Dosage concentration: water scale and corrosion inhibitor 25-35mg / L;
[0132] Temperature: about 25℃;
[0133] Time: 72 hours;
[0134] Operating conditions
[0135] Hanging piece and material: Standard test hanging piece (surface area: 28cm 2 Carbon steel hanging piece (density: 7.85g / cm 3 ), stainless steel hanging sheet (density: 7.93g / cm 3 )wait;
[0136] Test water quality: Make-up water: concentrated water with K=7.5;
[0137] Test water temperature: 45℃±1℃;
[0138] Rotation speed: 75 rpm;
[0139] Linear speed: 0.35 m / s;
[0140] Operating time: 96 hours.
[0141] 3. Test methods
[0142] According to the test conditions, fix the test piece on the rotating rack and rotate it in the test solution containing different concentrations of water scale and corrosion inhibitor. During the test, pay attention to maintaining the water quality conditions. After running for 72 hours, take out the test piece, clean the dirt on its surface, dry and weigh it, and calculate the corrosion rate to determine the best agent and the best dosage.
[0143] 4. Calculation formula:
[0144] Corrosion rate F = C × △ W / A × t × p
[0145] Where: F——corrosion rate (mm / y); △W——test piece corrosion weight loss (g); C——calculation constant 8.76×10 4 ; t——corrosion test time (h); A——surface area of the test piece (cm 2 ); p——test piece material density (g / cm 3 ).
[0146] The results are shown in Table 1.
[0147] Table 1
[0148]
[0149] It can be seen from the above table that the water scale and corrosion inhibitors prepared in Examples 1-4 of the present invention have good corrosion inhibition effects.
[0150] Take 10 mg of the water scale and corrosion inhibitor prepared in Examples 1-4 and Comparative Examples 1-7 and add them to a 1000 mL volumetric flask, dilute to scale with tap water (CaCO3 hardness of about 200 mg / L), and shake well to obtain a 1 mg / mL stock solution. Take a certain amount of the stock solution and 12.5 mL of 0.1 mol / L NaHCO3 solution in a 250 mL volumetric flask, dilute with 200 ml of tap water, then add 12.5 mL of 0.05 mol / L CaCl2 solution, dilute to scale with tap water, shake well, the CaCO3 hardness of the solution is about 450 mg / L, pour it into a beaker, cover the beaker mouth with a plastic bag, and place it in a 60±1°C water bath for 24 hours. After cooling, take out 50mL of the supernatant and add 5mL of NH4OH-NH4Cl buffer and 2-3 drops of KB indicator into a conical flask. Titrate with 0.02mol / L EDTA until the color changes from purple-red to blue-green and does not fade for 30s. This is the end point. Record the EDTA consumption.
[0151] Scale inhibition rate (%) = (V a -V o ) / (V b -V o )×100%
[0152] Where: V o V is the volume of EDTA consumed without adding scale inhibitor (mL); a V is the volume of EDTA consumed after adding the scale inhibitor (mL); b is the volume of EDTA (mL) consumed by the total calcium.
[0153] The results are shown in Table 2.
[0154] Table 2
[0155] Group Scale inhibition rate (%) Example 1 86.1 Example 2 88.4 Example 3 87.9 Example 4 89.7 Comparative Example 1 80.1 Comparative Example 2 78.0 Comparative Example 3 75.9 Comparative Example 4 76.2 Comparative Example 5 72.5 Comparative Example 6 68.7 Comparative Example 7 77.9
[0156] It can be seen from the above table that the water scale and corrosion inhibitors prepared in Examples 1-4 of the present invention have good scale inhibition effect.
[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A water scale and corrosion inhibitor, characterized in that: The following components are included in percentage by mass: 10-30% antiscalant; 35-40% hydrolyzed polymaleic anhydride; 12-20% acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer; 4-7.5% water-soluble zinc salt; and the balance of water.
2. The water scale and corrosion inhibitor according to claim 1, characterized in that: The scale inhibitor is at least one of polyepoxysuccinic acid, polyaspartic acid and modified oxidized starch.
3. The water scale and corrosion inhibitor according to claim 1, characterized in that: The water-soluble zinc salt is at least one of zinc sulfate, zinc nitrate, zinc chloride and zinc acetate.
4. The water scale and corrosion inhibitor according to claim 2, characterized in that: The preparation method of the modified oxidized starch is as follows: S1. Preparation of composite oxidized starch: corn starch, potassium permanganate and sulfuric acid were added to water, heated and stirred to react, the pH value of the solution was adjusted to, hydrogen peroxide was continued to be added dropwise, a catalyst was added, microwave treatment was performed, the reaction was continued at a temperature of 100 °C, the pH value of the solution was adjusted to 100 °C, filtration was performed, washing was performed, and drying was performed to obtain composite oxidized starch; S2. Grafting aspartic acid and lysine: adding composite oxidized starch to water, adding NHS and EDC, stirring to activate, adding aspartic acid and lysine, stirring to react, dialyzing, freeze-drying, and obtaining grafted composite oxidized starch; S3. Chlorination: adding the grafted composite oxidized starch to the ionic liquid, adding thionyl chloride, stirring the reaction, adding ethanol to precipitate, filtering, washing the solid, and drying to obtain a modified grafted composite oxidized starch; S4. Reaction with cyclodextrin: dissolving β-cyclodextrin in water, adding modified grafted composite oxidized starch and triethylamine, heating and stirring the reaction, centrifuging, washing, and drying to obtain cyclodextrin-modified grafted composite oxidized starch; S5. Ultrasonic treatment: adding the prepared cyclodextrin-modified grafted composite oxidized starch into water, ultrasonically treating it, and drying it to obtain modified oxidized starch.
5. The scale and corrosion inhibitor for water according to claim 4, characterized in that: In step S1, the mass ratio of corn starch, potassium permanganate, sulfuric acid, hydrogen peroxide and catalyst is 20-30:4-7:3-5:10-12:0.5-1, the catalyst is copper chloride or copper sulfate, the temperature of the heating and stirring reaction is 50-60°C, the time is 2-4h, the power of the microwave treatment is 1000-1500W, and the time is 1-3h.
6. The water scale and corrosion inhibitor according to claim 4, characterized in that: In step S2, the mass ratio of the composite oxidized starch, NHS, EDC, aspartic acid and lysine is 12-15:3-4:3-4:5-7:2-4, the dialysis bag used in the dialysis has a pore size of 8-12 KDa, and the dialysis time is 10-12 h.
7. The water scale and corrosion inhibitor according to claim 4, characterized in that: In step S3, the mass ratio of the grafted composite oxidized starch, dithionyl chloride and ionic liquid is 10:3-5:30-40, the stirring reaction time is 2-4 hours, and the ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium dihydrogen phosphate and 1-butyl-3-methylimidazolium hydrogen sulfate.
8. The water scale and corrosion inhibitor according to claim 4, characterized in that: In step S4, the mass ratio of β-cyclodextrin, modified grafted composite oxidized starch and triethylamine is 3-5:12-15:2-4, and the temperature of the heating and stirring reaction is 50-60° C. and the time is 3-5 hours.
9. The water scale and corrosion inhibitor according to claim 4, characterized in that: The power of the ultrasonic treatment in step S5 is 1500-2500W, and the time is 20-30min.
10. A method for preparing a water scale and corrosion inhibitor according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) adding hydrolyzed polymaleic anhydride to water, then adding a water-soluble zinc salt and stirring, mixing evenly to obtain a solution; (2) At room temperature, acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer and scale inhibitor are added to the solution and stirred evenly to prepare a scale inhibitor and corrosion inhibitor for water.
Citation Information
Patent Citations
Preparation method of phosphorus-free composite scale inhibitor
CN102452723B
A phosphorus-free corrosion and scale inhibitor and its preparation method
CN110342654B
Modified phosphorus-free scale inhibition and corrosion inhibitor and preparation method thereof
CN111003822A
Non-phosphorus scale inhibitor and preparation method thereof
CN113880266A
Modified starch and method for producing modified starch through heat treatment
CN118515787A